2016
DOI: 10.1186/s40902-015-0047-8
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on factors affecting the prognosis in oral cancer patients who underwent surgical treatment only

Abstract: BackgroundThis study was performed to evaluate their 5-year survival rates and identify the factors affecting the prognosis of oral cancer patients who had undergone surgical treatment only.MethodsAmong 130 patients who were diagnosed with malignant tumor of oral, maxillofacial, and surgical treated in the Department of Oral and Maxillofacial Surgery at Chonnam National University Hospital within a period from January 2000 to December 2010, for 11 years, 84 patients were investigated who were followed up for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…Two factors that were related to OS and DSS were pTNM stage and presence of neck node metastasis. Studies have shown that patients with advanced-stage disease have lower survival3. In fact, a recent study states that the most important clinical predictor of survival remains TNM stage at the time of diagnosis8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two factors that were related to OS and DSS were pTNM stage and presence of neck node metastasis. Studies have shown that patients with advanced-stage disease have lower survival3. In fact, a recent study states that the most important clinical predictor of survival remains TNM stage at the time of diagnosis8.…”
Section: Discussionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) is a common malignancy worldwide, with regional variations in incidence and mortality123. The most common risk factors associated with OSCC are tobacco and alcohol abuse4; however, the incidence in younger than 40 years without tobacco and alcohol abuse has increased5.…”
Section: Introductionmentioning
confidence: 99%
“…Low-grade MEC is surgically excised in a single piece along with the involved underlying mucosa and bone for an adequate tumor-free margin5. High-grade MEC has local infiltration and regional lymph node metastasis1415, requiring wider surgical resection with postoperative radiotherapy or chemotherapy116. Lymph node metastasis can occur in low-grade MEC1.…”
Section: Discussionmentioning
confidence: 99%
“…These challenges include the lack of systematic documentation of the disease (<2% of Asian's population is covered by population‐based registries (Ferlay et al, 2015), high use of smoked and smokeless tobacco (Ansara et al, 2013; Eriksen, Mackay, Schluger, & Islami, 2015) and limited access to diagnosis and treatment to name a few. Diagnosis at an early disease stage improves oral cancer survival, thus there is a critical need for effective strategies in promoting early detection (Ghani et al, 2019; Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%